Analisis Persepsi Harga Pada Hp Iphone di Kalangan Masyarakat - Rohmadi; Makhfudoh; Syamsul Hidayat (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
In this modern era, business growth is very rapid. Various businesses are developing everywhere, the number of prices and quality of products become various, making market competition fierce. The growth of technology can also make a big impact on human life, one of which is the growth in the field of smartphone technology such as smart phones. A smartphone is a smart telecommunications device that unites the functions of a mobile phone with various additional features, such as computing capabilities, internet connection, digital camera, and various software applications. The purpose of this study is to gain a better understanding of how customers assess product prices. For this study, a quantitative method was used, and the sample consisted of 343 carenang residents. The slovin formula was also used as a sampling technique. In this study, multiple linear regression analysis was used with significant results. shows that the interest in buying an iPhone is influenced by perceived price and product value